Characterization of the TATA-less core promoter of the cell cycle-regulated cdc25C gene. - Körner, K (1997)
The TATA- and Inr-less promoter of the human cdc25C gene is regulated during the cell cycle through binding of a repressor to two contiguous promoter-proximal elements, the CDE and CHR. In this study we have characterized in detail the region of the cdc25C promoter immediately downstream of these elements. Several lines of evidence suggest that this region of approximately 60 bp acts as the core promoter. This sequence: (i) harbors most of the transcription initiation sites; (ii) possesses basal promoter activity in vivo ; (iii) shows no stable protein binding in vivo as indicated by genomic dimethyl sulfate and phenanthroline copper footprinting; (iv) contains single-stranded regions in vivo as shown by potassium permanganate footprinting; (v) is hypersensitive to DNase I cleavage in permeabilized cells. Mutational analysis of the core promoter revealed the presence of three sites which play a role in transcription. Two of these sites were found to represent low affinity binding sites for transcription factors of the Sp1 family. Mutation of these sites led to decreased levels of transcription, while their alteration to canonical Sp1 sites impaired cell cycle regulation. Thus the transient interaction of Sp1 with the core promoter appears to be necessary for maximal transcription without perturbing cell cycle regulation.